EFFECT OF DIALYSATE TEMPERATURE ON HEMODYNAMIC STABILITY AMONG HEMODIALYSIS PATIENTS (Iraqi Journal of Medical Sciences, 2016)
Background: Hypotension is one of the complications of hemodialysis treatment. It increases morbidity and mortality and can compromise the dialysis efficacy. Cooling the dialysate below 36.5°C is an important factor that contributes to hemodynamic stability in patients during hemodialysis.Objective:To assess the effect of dialysate temperature on hemodynamic stability during hemodialysis sessions, post dialysis fatigue and the adequacy of dialysis.Methods: A total of 40 patients were assessed during six dialysis sessions; in three sessions, the dialysate temperature was (37 °C) and in three other sessions, the dialysate temperature was (35 °C). Specific scale questionnaires were used in each dialysis session, to evaluate the symptoms during the dialysis procedure as well as post-dialysis fatigue, and respective scores were noted. Blood pressure, heart rate, temperature were recorded. Also dialysis efficacy using Kt/v, urea reduction ratio were measured.Results:The results showed that usage of low dialysate temperature was associated with the following : higher post dialysis systolic blood pressure (P < 0.05) and lower post dialysis heart rate (P < 0.05), better intra-dialysis symptoms score and post-dialysis fatigue scores (P < 0.05 and P < 0.05, respectively), shorter post-dialysis fatigue period (P < 0.05) as well as Similar urea removal and Kt/V .Conclusion:Cool dialysis is an important factor in hemodynamic stability during hemodialysis. Also it improves symptoms during and after hemodialysis. Cool dialysis has no effect on adequacy of dialysis.Key words: Hemodialysis, Cool dialysate, Hypotension, Hemodynamic
Keywords: Hemodialysis; Cool dialysate; Hypotension; Hemodynamic